Battleships - Preston, Antony, 1938-2004. (Greenwich, Conn. : Bison Books Ltd., 1982)
Profusely illustrated text describes the development of the battleship and its role in naval history.
Wooden walls and ironclads -- Sovereigns of the seas -- Gunnery and the dreadnought -- Ready for war -- Line of battle -- The Washington Treaty -- Atlantic and Mediterranean -- Vulnerable giants -- The end of an era?
Includes index.
Keywords: Battleships; Armored vessels